Risk Factors and Prevalence of mcr-1-Positive Escherichia coli in Fecal Carriages Among Community Children in Southern Taiwan - Wu, Pin-Chieh; Cheng, Ming-Fang; Chen, Wan-Ling; Hung, Wan-Yu; Wang, Jiun-Ling; Hung, Chih-Hsin (Frontiers in Microbiology, 2021)
Colistin is the last resort antimicrobial for treating multidrug-resistant gram-negative bacterial infections. The plasmid-mediated colistin resistance gene, mcr-1, crucially influences colistin’s resistance transmission. Human fecal carriages of mcr-1-positive Escherichia coli (E. coli) were detected in many regions worldwide; however, only a few studies have focused on children. Therefore, we identified the prevalence and risk factors of mcr-1-positive E. coli in fecal carriages among community children in Southern Taiwan. In this study, 510 stool samples were collected from April 2016 to August 2019 from the pediatric department at a medical center in Southern Taiwan. These samples were collected within 3 days after admission and were all screened for the presence of the mcr-1 gene. Diet habits, travel history, pet contact, and medical history were also obtained from participants to analyze the risk factors of their fecal carriages to mcr-1-positive E. coli. Antimicrobial susceptibility testing was determined using the VITEK 2 system and the broth microdilution test. Twelve mcr-1-positive E. coli. were isolated from 2.4% of the fecal samples. Through multivariate analysis, frequent chicken consumption (at least 3 times per week) had a significantly positive association with the presence of mcr-1-positive E. coli in fecal carriages (adjust odds ratio 6.60, 95% confidence interval1.58– 27.62, p = 0.033). Additionally, multidrug resistance was more common in mcr-1-positive E. coli. (75.0% vs. 39.5%, p = 0.031) than in non-mcr-1-positive Escherichia coli. Furthermore, the percentage of extraintestinal pathogenic E. coli in mcr-1-positive isolates was 83.3%. Some multi-locus sequence types in our mcr-1-positive E. coli were also similar to those isolated from food animals in the literature. The prevalence of fecal carriages of mcr-1-positive E. coli was low among community children in Southern Taiwan. Our data shows that chicken consumption with a higher frequency increases the risk of mcr-1-positive E. coli. in fecal carriages.